Comparación entre dos Métodos de Valoración de los Mapas de Retorno de la Variabilidad de la Frecuencia Cardíaca - Carrasco Sosa, S.; Gaitán González, J. M.; González Camarena, R.; Pereyra Cardona, G. (Revista Mexicana de Ingenieria Biomedica, 1999)
Return maps are useful tools in the non-linear analysis of the heart rate variability. The comparison between two quantification return maps methodology, statistical and geometrical, is contrasted. Their sympathetic-parasympathetic discrimination power was evaluated for five maneuvers. The RR interval series were obtained from the ECG in 12 individuals for five maneuvers of different sympathetic-parasympathetic activity levels. The return maps were obtained for one, three, and six beat-lags. The correlation coefficient (statistic method) and the dispersion over the transverse and longitudinal axes (geometrical method) were computed, as well as the ration and product of the latest. The log od the dispersion product was able to discriminate among all the maneuver contrasts. A high correlation was observed between the correlation coefficient and the geometric parameters. We conclude the return maps are an easy and confident technique to evaluate the sympathetic-vagal activity for the maneuvers used in this study. The geometric method is recommended to evaluate the return maps because of its high discriminative capacity and the adequate physiological interpretation.